Tertiary larger foraminifera from Guam - Cole, W. Storrs (William Storrs), 1902-1989 (Geology and hydrology of Guam, Mariana Islands., 1963)
"Description, distribution, and occurrence of species ranging from the Eocene to the Pleistocene, and correlation with faunas of Saipan, bikini, Eniwetok, Fiji, and the Malayan Archipelago."